LEARNING DIFFICULTIES AND COPING METHODS EMPLOYED BY ADOLESCENTS: A SCHOOL -BASED MIXED-METHODOLOGY STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Adolescence is a developmental stage marked by significant social, academic, and personal changes, during which individuals begin forming a clearer sense of identity. The World Health Organization defines adolescence as the period between ages 10 and 19, characterized by rapid physical, cognitive, and psychosocial development. During this time, many adolescents encounter many challenges, many of which include learning disparities. These difficulties often become more evident in early to mid-adolescence, as students are expected to manage increasingly complex academic demands, such as independent study, test-taking, and future planning, while also maintaining a balanced and healthy lifestyle. It's important to note that learning challenges experienced during adolescence can extend beyond just academic performance. They may influence an individual’s self-esteem, emotional well-being, motivation to learn, and overall ability to maintain healthy relationships with peers and family members. Aim: This qualitative study aimed to investigate adolescents’ perceptions of their learning difficulties. Of this includes their emotional experiences, different coping strategies, and their individual needs in order to support their learning. Method: A qualitative descriptive approach was used in this study. A group of 17 adolescents, aged 13 to 18, participated in semi-structured interviews guided by predetermined questions. These questions explored academic challenges, emotional responses, impacts on relationships, coping strategies, and expectations of support from school and family. Each interview lasted approximately 30 - 45 minutes and was conducted in a location of the participants' choosing to ensure comfort and privacy. After gaining consent, interviews were audio-recorded, transcribed, and analyzed using Braun and Clarke’s thematic analysis framework to identify recurring patterns from the data. All data was anonymized. Results: The analysis of the data revealed five key themes: the ongoing nature of academic struggles, the emotional burden associated with these challenges (for example: reduced confidence), the difference between avoidance and effortful coping, and the importance of supportive relationships when facing challenges such as academic difficulties. Additionally, participants highlighted the importance of support from both family and their schools. Through the analysis, key coping strategies were identified, including turning to friends and teachers for help, breaking tasks into smaller steps, repeated practice, temporarily avoiding the situation, and withdrawing emotionally. Conclusion: To conclude, academic struggles experienced by adolescents with learning difficulties were generally not viewed because of poor academic performance, but as a combination of emotional and social challenges. To combat these difficulties, the type of critical support that seemed to provide confidence and overall support included: teachers fostering a supportive environment, open and non-judgmental communication with family members, assistance from peers, and the usage of flexible academic strategies.